Abdominal compartment syndrome: rare occurrence due ureteric injury - Najman, Ahmad Farhan; Mohamed Sufian, Arif Rukaini; Abdul Rasid, Muhammad Hafiz; Azmi, Muhamad Zulhilmi; Abu Bakar, Intan Bazilah; Kamarulzaman, Mohd Nazli (OASK Publishers, 2025)
Compartment syndrome is a syndrome that can happened in any anatomical area with increased pressure in a confined body space, resulting in poor blood flow, cellular damage, and organ dysfunction. • One of it is abdominal compartment syndrome and it is a serious condition that occurs when the pressure in the abdominal cavity rises above 20 mmHg and causes endorgan damage [1,4]. • Abdominal compartment syndrome may occur after conditions such as peritonitis, intestinal obstruction, laparoscopic procedures, or abdominal tumors4. • Leakage from the urinary tract may cause accumulation of urine in the peritoneal cavity